Authorised Histories: Human Remains and the Economies of Credibility in the Science of Race - Roque, Ricardo (Kronos: Southern African Histories, 2020)
In this article, I approach the issues of missing data and testimony in the context of the history of race science, craniology, and collections of human remains housed in museums. In the context of comparative race science, human skulls were intended to be examined in association with short histories and biographical data about their pasts. I investigate how and why such documentation and historicising work formed part of a knowledge economy in the nineteenth century that, at the microscopic scale of the archival documents linked to the collections, was intended to verify the authority of human remains as testimonial evidence of distinct human races. I then show that the association of documents, narratives and historical information with collections of human skulls was a common and important practice in the field of ‘anthropology’ (which, in nineteenth-century usage, was referred to as the ‘science of race’, or ‘natural history of man’, and later renamed ‘physical anthropology’), and a significant part of its claims to scientificity. At the time, the notion of ‘race’, even in craniology (race science’s most paradigmatic manifestation), was more than a construct derived purely from the observation of human remains. In the context of such collections, ‘race’ was an artefact entangled in a network of documents, archives, and narratives associated with anatomical collections – its coming into being shaped, and was shaped by, how collectors, race scientists, and museologists produced, curated, and authenticated the histories and records of specific human skulls over time. I concentrate in this article on the relationship that the historiographic domain maintained with the production of credibility. That is, I focus on the authority of collectors’ testimonies, and on how the authenticity of these testimonies was managed within the field of the race science that was craniology.1 Historical documentation, including narratives about the pasts and the identities of collections, served as technologies that attested to the credibility of using the testimony of human remains as evidence in support of racial theories, genealogies, and taxonomies.